2004
DOI: 10.1007/bf02659621
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish real exchange rate under different currency regimes

Abstract: Real exchange rate, exchange rate regimes, cointegration,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Bahmani-Oskooee and Goswami (2005) explores that domestic and foreign price levels are not weakly exogenous in many countries. Larsson (2004) investigates the affiliation of Swedish real exchange rate with other currency regimes like Germany, this study is concluded with the support of Unit root test, cointegration, and ECM that there is long term association (cointegration) between real exchange rate and productivity of Sweden and Germany. But at the same time in the short run, the exchange rate regime has subjected for the dynamics of the real exchange rate.…”
Section: Empirical Studiesmentioning
confidence: 65%
“…Bahmani-Oskooee and Goswami (2005) explores that domestic and foreign price levels are not weakly exogenous in many countries. Larsson (2004) investigates the affiliation of Swedish real exchange rate with other currency regimes like Germany, this study is concluded with the support of Unit root test, cointegration, and ECM that there is long term association (cointegration) between real exchange rate and productivity of Sweden and Germany. But at the same time in the short run, the exchange rate regime has subjected for the dynamics of the real exchange rate.…”
Section: Empirical Studiesmentioning
confidence: 65%
“…Larsson (2002) tests this and finds some support for a regime-dependent behavior in the SEK/DEM real exchange rate. 10 The constants are unknown since we do not know from the estimated equations what part of the estimated constant pertains to the cointegrating relation.…”
Section: Real Exchange Ratesmentioning
confidence: 84%
“…Clarida and Prendergast (1999) analyse dynamic effects of fiscal policy shocks on the real exchange rate for Germany, US, and Japan, and they find that the real exchange rate appreciates for several years after an expansionary fiscal shock. Larsson (2002) finds that higher growth in Swedish log government consumption relative to German log government consumption causes a nominal depreciation under a floating regime, who is playing a role as a shock absorber. Furthermore, Chinn (1997) finds evidence of cointegration between the real exchange rate, manufacturing productivity and government spending for the Canadian Dollar, the Deutschemark, Yen and Pound.…”
Section: A Simple Model Of Fixed Exchange Rates and Fiscal Policymentioning
confidence: 98%